Physical and metabolic requirements of elite military divers - Kelly, Karen R.; Palombo, Laura J.; Givens, Andrea C.; Bernards, Jake R.; Bennett, Daniel (Frontiers in Physiology, 2025)
IntroductionThe purpose of this investigation was to characterize the physical and physiological profile of elite military divers.MethodsThe profile included anthropometric (height, weight, fat free mass, fat mass, percent body fat), performance testing (V˙o2max, 3-mile run (4.82 km), 0.5-mile swim (0.8 km), weighted pull-ups, estimated 1-rep max for bench and deadlift, and broad jump) and physiological functioning via the awake response (cortisol, testosterone, and dehydroepiandrosterone).ResultsAnthropometric and performance results presented as MEAN ± SE include: age: 28.0 ± 0.5 years; height: 70.7 ± 0.3 in (179.6 ± 0.8 cm); weight: 193.3 ± 2.0 lbs (87.9 ± 0.9 kg); body fat percentage: 18.2% ± 0.6%; V˙o2max: 55.3 ± 0.7 ml kg -1 · min-1; bench-press 1RM: 278.7 ± 7.7 lbs (126.8 ± 3.5 kg); deadlift 1RM: 397.9 ± 10.6 lbs (172.7 ± 4.8 kg). Significant associations were found between anthropometric measures and measures of magnitude in testosterone and DHEA. Physical performance metrics showed significant associations with summary parameters in all salivary hormones, with quartile splits yielding significant differences in absolute DHEA and 1RM deadlift (F (3, 30) = 2.97, p = 0.048), AUCg testosterone and broad jump (F (3, 37) = 2.86, p = 0.05), and AUCg T:C ratio and 25lb weighted pull ups (F (3, 35) = 4.66, p = 0.008). Linear mixed models revealed a significant effects of evolution/collection time point on AUCg DHEA at time points three (B = −2735.96, t (177.32) = −2.39, p = 0.018) and four (B = −3089.92, t (178.97) = −2.7, p = 0.008); and on peak testosterone at time point five (B = 28.12, t (215.4) = 2.4, p = 0.017) with reference to time point one.ConclusionThe data presented herein indicate there are certain periods of training that elicit significant changes in testosterone and DHEA while cortisol remains stable throughout the training cycle. To our knowledge, this effort is the first to document changes in stress biomarkers over time in elite military divers.